Efficacy of fungicides and biocontrol agents against Bipolaris oryzae, the causal agent of brown spot of rice - MAURYA, NIMISHA; KUMAR, BIJENDRA; SINGH, R P; TEWARI, RASHMI; BISHT, ASHISH SINGH (The Indian Journal of Agricultural Sciences, 2025)
Rice faces significant losses by the brown spot disease caused by Bipolaris oryzae, can be mitigated by the application of fungicides and biocontrol agents for effective disease management. This study found that Tebuconazole (25.9% ec) was the most effective fungicide, while a combination of T. harzianum and Pseudomonas fluorescens offered the best disease control and highest yield in the field. The biocontrol agents also enhanced the defense enzyme activity (PAL, POD, PPO). These findings support an integrated disease management strategy that uses both fungicides and biocontrol agents for optimal disease control and improved yield.